Selection of antihypertensive drugs from the perspective of clinical pharmacology - Victor Ghicavii; Nicolae Bacinschi; Lilia Podgurschi; Lucia Turcan; Marin Chianu (The Moldovan Medical Journal, 2018)
Background: The rational use of medicines remains one of the most important directions of public health, especially in socio-medical diseases, including arterial hypertension. Material and methods: The study involved 28 cardiologists and 84 internists who, based on a set of questionnaires, expressed their opinion on ambulatory treatment of patients with arterial hypertension. Also 21 internists, 6 cardiologists and 6 obstetrician-gynecologists expressed their opinion on treatment of pregnancy-induced hypertension. Results: Cardiologists and internists recommended angiotensin-converting-enzyme inhibitors (ACE inhibitors) in 28% of cases, diuretics – in 23% of cases, beta-blockers (BB) – in 20, 4% of cases, calcium channel blockers (CCB) – in 13.7% of cases, angiotensin receptor blockers (ARB) – in 13.6% of cases for ambulatory treatment of patients with arterial hypertension. The antihypertensive drugs from other pharmacological groups (with central action, alpha-blockers, arteriodilators, sympatholytics, etc.) were prescribed in only 1.3% of patients. On treatment of hypertension in pregnancy showed that all physicians – 100% recommended as first-line agent for treatment of hypertension during pregnancy centrally acting antihypertensive drug Methyldopa. For second-line treatment they recommended CCB – in 36.36% of cases, alpha-adrenoblockers – in 24.24% of cases, BB – in 21.21% of cases, diuretics – in 12.12% of cases and 3% for ACE inhibitors and ARB. For treatment pre-eclampsia and eclampsia seizures in 84.85% of cases is recommended Magnesium sulfate and 15.15% mention labetalol, hydralazine and sodium nitroprusside. Conclusions: ACE inhibitors, diuretics, BAB, CCB and ARB have been first-line drugs in the arterial hypertension (AHT) treatment. For treatment of pregnancy-induced hypertension physicians recommended centrally acting antihypertensive drug Methyldopa. For second-line treatment they recommended calcium channel blockers (CCB), alpha-adrenoblockers, beta-blockers (BB) and diuretics. As third-choice in treatment of severe hypertension in preeclampsia are selected direct vasodilators as hydralazine, labetalol, sodium nitroprusside, and the most widely used in preeclampsia and eclampsia remains magnesium sulfate.